Workshop on the Caribbean Cooperative rice research network / edited by Federico Cuevas (CIAT CaliCO, 1986)
Workshop to prepare a research program of the most important problems of common interest to rice producing Caribbean countries. Contains country reports on the rice situation in 8 territories. Summarizes the rice situation in the Caribbean. Concludes that a well coordinated regional effort is needed in rice research in order to achieve national goals in rice production. Recommends that collaboration be encouraged among countries by the creation of a cooperative Caribbean rice research network. Outlines objectives, strategy, activities, organization and financing of such a network.
Includes bibliographical references